2022
DOI: 10.3390/agronomy12081912
|View full text |Cite
|
Sign up to set email alerts
|

Driving Factor Identification for the Spatial Distribution of Soil Salinity in the Irrigation Area of the Syr Darya River, Kazakhstan

Abstract: Soil salinization has become a worldwide issue affecting agricultural development. Statistical methods and spatial analysis were used to analyze the degree and type of saline soils and their spatial distribution. The driving factors of soil salinity were explored using Geodetetcor models. In this study, 84 soil samples were collected from a 0–20 cm soil layer, and the total salt concentration and salt ion composition were measured. The results of statistical analysis and cluster analysis showed that SO42− and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Near the larger drainage channels, salinity levels are higher. These results suggest a serial movement of salt masses over long times (Duan et al, 2022;Wang et al, 2018).…”
Section: Long Term Landscape Management Impacts On Soil and Water Sal...mentioning
confidence: 67%
“…Near the larger drainage channels, salinity levels are higher. These results suggest a serial movement of salt masses over long times (Duan et al, 2022;Wang et al, 2018).…”
Section: Long Term Landscape Management Impacts On Soil and Water Sal...mentioning
confidence: 67%
“…Rice cultivation in the lower reaches of the Syrdarya River performs the reclamation function for saline irrigated agricultural lands, occupying up to 90 thousand ha annually (Funakawa et al, 2000;Duan et al, 2022). The use of phytop 8.67 and the development of technology for its application for rice will save the cost of its application, and reduce the rate of application of nitrogen fertilizers and the environmental burden on the ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The interdependent relationship between water quality and soil erosion cannot be overstated [1]. The statistical analysis found that the irrigated lands in the Syrdarya river basin had the highest levels of salinity, with SO4 2− being the main anion and Ca 2+ as the main cation contributing to this [2]. Salinization will contribute to the erosion and degradation of soil which can be ascribed to the vegetation dynamics.…”
Section: Introductionmentioning
confidence: 99%